2003
DOI: 10.1007/s11882-003-0045-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between atopy and bacterial infections

Abstract: Atopy in its most common forms (asthma, allergic rhinitis, and atopic dermatitis) has a significant impact on society in terms of health care costs and quality of life. Aside from having significant morbidity from these diseases, patients with atopy have also been noted to have a high incidence of comorbidities, including bacterial infections such as otitis media and sinusitis. In this paper, current evidence is reviewed that supports the close associations among allergic rhinitis and the two commonly diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…As in asthma, eosinophils are also characteristically implicated in seasonal and perennial rhinitis [6], chronic rhinosinusitis [7], nasal polyposis [8], idiopathic eosinophilic syndromes and atopic dermatitis [9][10][11][12]. Accumulation of eosinophils also occurs in some other disorders such as parasitic infections and cancer [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…As in asthma, eosinophils are also characteristically implicated in seasonal and perennial rhinitis [6], chronic rhinosinusitis [7], nasal polyposis [8], idiopathic eosinophilic syndromes and atopic dermatitis [9][10][11][12]. Accumulation of eosinophils also occurs in some other disorders such as parasitic infections and cancer [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Mast cells are common in the normal middle ear (ME), where they account for the most numerous population of resident leukocytes by far, [17][18][19] a finding that has supported previous attempts to connect allergy to the expression of otitis media. [20][21][22] Although allergic challenge has been shown to induce ME effusion, [23][24][25] a link between atopy and otitis media in human beings has been difficult to establish.…”
mentioning
confidence: 99%
“…Thirdly, different inflammatory response to infections and high incidence of comorbidity with bacterial infections including sinusitis (Mucha and Baroody 2003) in atopic subjects may be a contributing factor in pathogenesis of bronchiectasis. It has been reported that virus-induced inflammatory changes in upper respiratory tract infections are more prolonged in atopic than in nonatopic subjects (Corne et al 2001), suggesting that it might have resulted in higher probability of bronchiectasis.…”
Section: Discussionmentioning
confidence: 99%